P419 Outcomes at one year after sequential use of high-dose tofacitinib following infliximab in Acute Severe Ulcerative Colitis. (30th January 2023) - Eqbal, A; Hilley, P; Gilmore, R; Li Wai Suen, C; Choy, M; De Cruz, P
Abstract: Background: Acute Severe Ulcerative Colitis (ASUC) remains a significant cause of morbidity faced by up to 25% of patients with ulcerative colitis at some point during their disease course. We present the outcomes up to 1 year after the novel use of high dose tofacitinib, in patients with steroid refractory ASUC after failing to respond to infliximab. Methods: Eleven patients with ASUC who were treated with high dose sequential tofacitinib [10mg three times daily (TDS)] after failing to respond to infliximab between 2019-2021 were identified at an Australian tertiary centre. Results: Nine of 11 patients demonstrated a clinical and biochemical response to treatment during admission. All 9 patients remained colectomy free at both 6 and 12 months. At 6 months the median Mayo score was 1 [range 0-7]. At 12 months the median Mayo score was 1 [range 0-6]. No patients experienced venous thromboembolic events or major infective complications. Conclusion: High dose tofacitinib may be a safe and effective agent in the treatment of steroid refractory ASUC after failing to respond to infliximab. Prospective studies are required to explore the use of tofacitinib in ASUC before it can be routinely recommended as salvage therapy.